NMR structure determination of the protein NP_344798.1 as the first representative of Pfam PF06042 - Mohanty, Biswaranjan (J Biomol NMR, 2014)
We present the NMR structure determination of the protein NP_344798.1, which forms a CCA-adding enzyme head-domain architecture and is the first structural representative of the Pfam protein family PF06042. Its structure can now serve as a template for homology modeling of the other 785 members of this protein family. With 191 residues, NP_344798.1 is the largest single-domain protein structure determined so far with the J-UNIO protocol for automated NMR structure determination. The present work thus also shows that J-UNIO based exclusively on automated projection spectroscopy (APSY) and 3D heteronuclear-resolved [(1)H,(1)H]-NOESY experiments, can successfully be used to obtain high-quality NMR structures of protein domains with up to 200 residues.